KOMUNIKASI PEMASARAN TERPADU STARBUCKS BALI PADA PROGRAM “STARBUCKS GREENER NUSANTARA” SEBAGAI PERUSAHAAN YANG RAMAH LINGKUNGAN - Cahyani, Siva Eka Putri; Purnawan, Ni Luh Ramaswati; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2021)
The "Starbucks Greener Nusantara" is a program specifically launched by Starbucks Indonesia on the island of Bali in line with the global vision of becoming a company that is concerned with Bali Governor Regulation Number 97 of 2018 concerning the Limitation of Single-Use Plastic Waste. This program was launchedin accordance with the current era of the industrial revolution 4.0 related to green marketing. The purpose of this research is to find out and describe Starbucks Bali integrated marketing communication in the "Starbucks Greener Nusantara" program as an eco friendly company. The approach taken in this research is descriptive qualitative approach. The researcher determined the informant by using purposive sampling technique.The result of this research is the "Starbucks Greener Nusantara" program using the 4P classification (product, place, price, promotion) and IMC strategy there are five elements of a promotion mix strategy with the same message consistency in it. Keywords: Integrated Marketing Communication, IMC, Starbucks Greener Nusantara, Starbucks Bali.